2010
DOI: 10.1097/mpg.0b013e3181ae3610
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualization and Treatment of Chronic Abdominal Pain in Pediatric Gastroenterology Practice

Abstract: The evolution and dissemination of the Rome criteria for the past 15 years have not substantially changed evaluation or treatment practices for children with abdominal pain. Many areas of inconsistency and controversy remain. More focused research is needed to better understand this common pain condition and to establish an effective treatment program that can be disseminated across practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 9 publications
1
68
1
2
Order By: Relevance
“…A recent study showed that only a small percentage of pediatric gastroenterologists (14%) recommended lifestyle changes in patients with FGIDs. 27 Even though patients in our study were seen at a tertiary care center, none of the obese patients had documented counseling on dietary and lifestyle modifications during their visits. As we learn more about the relationship between these two prevalent conditions in childhood, it seems reasonable to intervene as early as possible to potentially prevent the development of functional abdominal pain, and if not possible to improve the response to standard medical treatment precluding abdominal pain from becoming a chronic condition.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that only a small percentage of pediatric gastroenterologists (14%) recommended lifestyle changes in patients with FGIDs. 27 Even though patients in our study were seen at a tertiary care center, none of the obese patients had documented counseling on dietary and lifestyle modifications during their visits. As we learn more about the relationship between these two prevalent conditions in childhood, it seems reasonable to intervene as early as possible to potentially prevent the development of functional abdominal pain, and if not possible to improve the response to standard medical treatment precluding abdominal pain from becoming a chronic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, physicians treating CAP work to ensure that there are no red flags for diagnosis of an organic disease and provide reassurance that the condition is nothing to worry about, brief education on the biopsychosocial model for chronic abdominal pain, and referral out for cognitive-behavioral therapy, hypnotherapy, or another treatment aimed at stress reduction and return to function [27]. For some caregivers, this approach may seem inadequate to address their concerns about their child's symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…When surveyed, approximately 65% of paediatric gastroenterologists reported routinely referring to a mental health practitioner when no 'organic' cause of abdominal pain is identified [1]. However, studies indicate that only 40-60% of paediatric patients referred for mental health services by a physician follow through with this referral [5,6].…”
Section: International Journal Of Integrated Care -Vol 10 2 August mentioning
confidence: 99%
“…However, this approach has not been wholly satisfactory. In a recent survey, approximately 60% of paediatric gastroenterologists report a successful outcome in less than half of their patients [1]. One difficulty with the traditional medical…”
Section: Introductionmentioning
confidence: 99%